ҚАЗАҚСТАНДАҒЫ ФРАНЧАЙЗИНГТІҢ ҚАЗІРГІ ЖАҒДАЙЫ ЖӘНЕ ОНЫ ДАМЫТУ МӘСЕЛЕЛЕРІ - Каримова, М Д (Journal of Economic Research & Business Administration, 2015)
In this article condition and issue of franchise development in Kazakhstan at present is considered.